Role of the Extracellular Signal-Regulated Kinase 1/2 Signaling Pathway in Ischemia-Reperfusion Injury - Kong, Tingting; Liu, Minghui; Ji, Bingyuan; Bai, Bo; Cheng, Baohua; Wang, Chunmei (Frontiers in Physiology, 2019)
Extracellular signal-regulated kinase 1/2 (ERK1/2), an important member of the mitogen-activated protein kinase family, is found in many organisms, and it participates in intracellular signal transduction. Various stimuli induce phosphorylation of ERK1/2in vivo and in vitro. Phosphorylated ERK1/2 moves to the nucleus, activates many transcription factors, regulates gene expression, and controls various physiological processes, finally inducing repair processes or cell death. With the aging of the population around the world, the occurrence of ischemia-reperfusion injury (IRI), especially in the brain, heart, kidney, and other important organs, is becoming increasingly serious. Abnormal activation of the ERK1/2 signaling pathway is closely related to the development and the metabolic mechanisms of IRI. However, the effects of this signaling pathway and the underlying mechanism differ between various models of IRI. This review summarizes the ERK1/2 signaling pathway and the molecular mechanism underlying its role in models of IRI in the brain, heart, liver, kidneys, and other organs. This information will help to deepen the understanding of ERK1/2 signals and deepen the exploration of IRI treatment based on the ERK1/2 study.